The Financial Resilience of IDX-MES BUMN17 Companies in Response to COVID-19 Crisis and Economic Recovery - Susanto, Arva Athallah; Suprayitno, Aryadimas (Forum Kerjasama Pendidikan Tinggi, 2025)
The COVID-19 pandemic has significantly affected global financial markets, reinforcing the need for investments that are not only financially beneficial, but also prioritize ethical and sustainable principles. In Indonesia, the focus on economic sustainability is increasing through the Islamic capital market and state-owned companies, which play a strategic role in the country's economy. However, research on the financial performance and market capitalization of BUMN companies amid the COVID-19 pandemic is limited. This study aims to analyze the effect of these factors on the share prices of state-owned companies in Indonesia, specifically on IDX-MES BUMN17, during and after the COVID-19 pandemic. Using regression and trend analysis through Statistical Package for the Social Sciences (SPSS) software, we will explore the relationship between financial performance variables and market capitalization on the share prices of BUMN companies. This analysis will cover periods of economic crisis and recovery, focusing on how capital market dynamics affect investor behavior and the future value of BUMNs' shares, particularly in the context of Islamic economics. It is hoped that this research can provide a deeper understanding of capital markets and sustainable investment in Indonesia, as well as make important contributions to investment decision-making and risk management in the future.